Odpowiedź :
Odpowiedź:
licze na naj:)
Szczegółowe wyjaśnienie:
x - 2x - 3/3 = x + 2/5 + 2
-2x - 1 = 2/5 + 2
-2x - 1 = 12/5
-2x = 12/5 + 1
-2x = 17/5 l:(-2)
x = -17/10
-17/10 - 2 * (-17/10) - 3/3 = -17/10 + 2/5 + 2
17/5 - 1 = 2/5 + 2
12/5 = 12/5
prawda
Odpowiedź:
x- 2x -3/3 = x +2/5 +2
x -2x -x = 2/5 +2 +1
-2x= 3 i 2/5 /*(-1)
2x= - 3 i 2/5 /:2
x= - 17/5:2= - 17/5 *1/2= - 17 /10
x= - 17 /10= - 1 i 7/10
spr... -1 i7/10 - 2*(-17/10) - 1= - 17/10 +2/5 +2
-1 i 7/10 + 34/10 -1= 2 i 4/10-17/10
- 2 i 7/10 +3 i 4/10 = - 1 i 7/10 +1 i 14/10
-2 i 7/10 +2 i 14/10= 7/10
7/10=7/10
L=P
Szczegółowe wyjaśnienie: